2012
DOI: 10.1096/fj.12-218990
|View full text |Cite
|
Sign up to set email alerts
|

Flavones induce neutrophil apoptosis by down‐regulation of Mcl‐1viaa proteasomal‐dependent pathway

Abstract: Neutrophil apoptosis and subsequent nonphlogistic clearance by surrounding phagocytes are key to the successful resolution of neutrophilic inflammation, with dysregulated apoptosis reported in multiple human inflammatory diseases. Enhancing neutrophil apoptosis has proresolution and anti-inflammatory effects in preclinical models of inflammation. Here we investigate the ability of the flavones apigenin, luteolin, and wogonin to induce neutrophil apoptosis in vitro and resolve neutrophilic inflammation in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 69 publications
2
70
0
Order By: Relevance
“…In addition, p53 reduces Bcl-2 transcription (41). Flavones induce caspase-dependent apoptosis in A549 cells (42) and primary human neutrophils (43). Our present study showed that metformin, flavone and combination induced apoptosis by decreasing Bcl-2, increasing Bax and cleaved caspase3 protein level.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, p53 reduces Bcl-2 transcription (41). Flavones induce caspase-dependent apoptosis in A549 cells (42) and primary human neutrophils (43). Our present study showed that metformin, flavone and combination induced apoptosis by decreasing Bcl-2, increasing Bax and cleaved caspase3 protein level.…”
Section: Discussionsupporting
confidence: 55%
“…5E). Neutrophils are exposed to inflammatory mediators at sites of inflammation that may extend their life span by delaying apoptosis (28). Because SIV induced apoptosis in vivo, in a milieu exposure to prosurvival factors, we investigated the ability of SIV to counteract the prosurvival effects of LPS.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro experiments to evaluate neutrophil apoptosis Neutrophils were isolated from human peripheral blood from healthy donors (Ethics Committee of the Universidade Federal de Minas Gerais, BrazilInstitutional Review Board Project number 0319.0.203.000-11) by using histopaque gradient (Histopaque 11191 and 10771; Sigma-Aldrich) as described previously (28). Neutrophils (1 3 10 6 cells/well) were resuspended in RPMI 1640 medium, seeded in 24-well culture plates (BD Biosciences), and incubated at 37˚C in a 5% CO 2 atmosphere.…”
Section: Evaluation Of Leukocyte Apoptosis and Efferocytosismentioning
confidence: 99%
“…The flavone wogonin (5,7-dihydroxy-8-methoxyflavone) has been proposed to have anticancer and antiinflammatory properties (18,19). Recently, we showed that flavones, including wogonin, were able to drive neutrophil apoptosis by downregulating the prosurvival Bcl-2 family member Mcl-1.…”
mentioning
confidence: 99%